Penerapan Prinsi Building As Nature Pada Youth Center DiKota Dumai - Muhammad Syifa (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2020)
Dumai City is a city in Riau Province, Indonesia, about 188 km from Pekanbaru City. Dumai is the city with the third largest administrative area in Indonesia, after the City of Palangka Raya and the City of Tidore Islands. The city started as a small hamlet on the east coast of Riau Province. The average height is 3 meters above sea level. The Dumai City region has a tropical climate with rainfall between 100-300 cm and a temperature of 24-30 ° C with peat swamp soil conditions. In the City of Dumai itself has problems in places where people and some communities gather and family reclamation sites.In this title, "YOUTH CENTER" is taken which by applying the principle of "BUILDING AS NATURE" as a theory of the design of the building and is also included as one of the principles of the ORGANIC ARCHITECTURE. The Oral Center is a place where young people can meet and participate in various activities, such as basketball, table tennis, games, and artistic activities. There are also Youth Clubs or Centers varying in their activities that are diverse in cultural contexts, with the creation of "YOUTH CEBTER" this can reduce problems for the community in Dumai City today.